2018
DOI: 10.18632/oncotarget.26089
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-beta is a potential target for triple negative breast cancer treatment

Abstract: Triple Negative breast cancer (TNBC) is a subtype of breast cancer that lacks the expression of estrogen receptor (ER), progesterone receptor, and human epidermal growth factor receptor 2. TNBC accounts for 15-20% of all breast cancer cases but accounts for over 50% of mortality. We propose that Estrogen receptor-beta (ERβ) and IGF2 play a significant role in the pathogenesis of TNBCs, and could be important targets for future therapy.Tissue microarrays (TMAs) from over 250 TNBC patients' were analyzed for ERβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 71 publications
1
54
1
Order By: Relevance
“…Studies have shown that isoflavones preferentially bind to and transactivate ERβ rather than ERα, which induces conformational changes in the receptor. Austin et al (2018) showed that ERβ could be targeted by isoflavone compounds in TNBC tumors (Austin et al., 2018). In a randomized placebo‐controlled clinical trial on postmenopausal women, Palomares et al.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that isoflavones preferentially bind to and transactivate ERβ rather than ERα, which induces conformational changes in the receptor. Austin et al (2018) showed that ERβ could be targeted by isoflavone compounds in TNBC tumors (Austin et al., 2018). In a randomized placebo‐controlled clinical trial on postmenopausal women, Palomares et al.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ERβ1 was found to be associated with significantly worse 5-year OS in TNBC patients [55]. Moreover, a study indicated that patients with TNBC and positive ERβ expression exhibited poorer DFS [54] and decreased recurrence-free survival (RFS) regardless of chemotherapy use [51].…”
Section: Prognostic Value Of Erβ In Breast Cancermentioning
confidence: 99%
“…Adiponectin is responsible for switching macrophages from the M1 to M2 phenotype, thus improving the inflammatory profile (Li et al 2011). By contrast, human BC cells express adiponectin receptors (AdipoR1, R2), which, when present at low concentrations can promote ER+ BC proliferation, but reduce triple-negative breast cancer cell (TNBC) growth in the presence of 17-β estradiol (Dieudonne et al 2006, Pfeiler et al 2008, Austin et al 2018. This can be explained by the downstream signaling crosstalk between adiponectin and estrogen receptors in modulating AMPK and MAPK pathways respectively in TNBC and ER+ BC cells (Gelsomino et al 2019).…”
Section: Role Of Inflammatory Adipo-cytokinesmentioning
confidence: 99%